Successful Anesthetic Management of a Cesarean Section in a Patient with Cardiomyopathy and Cardiogenic Shock: A Case Report - Alta Ikhsan Nur; Nopian Hidayat; Novita Anggraeni; Sony (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Cardiomyopathy in pregnancy is a rare but serious condition that can lead to significant maternal and fetal morbidity and mortality. Anesthetic management of these patients is challenging due to the complex interplay of physiological changes and the potential for hemodynamic instability. This case report describes the successful anesthetic management of a cesarean section in a patient with cardiomyopathy and cardiogenic shock. Case presentation: A 29-year-old woman with cardiomyopathy and cardiogenic shock presented for emergency cesarean section at 36-37 weeks gestation. She had a history of global hypokinetic, left ventricular and atrial dilatation, and an ejection fraction (EF) of 32%. She was also in atrial fibrillation. Epidural anesthesia was selected due to its lower risk of complications compared to general anesthesia. The patient was carefully monitored throughout the procedure, and her hemodynamics were maintained with a combination of fluids and inotropes. The surgery was successful, and the patient delivered a healthy baby boy. Conclusion: This case report demonstrates that successful anesthetic management of cesarean section is possible in patients with cardiomyopathy and cardiogenic shock. Careful planning, close monitoring, and a multidisciplinary approach are essential for a positive outcome.